RETRACTED: LAYANAN PERPUSTKAAN PERGURUAN TINGGI DI MASA AWAL PANDEMI COVID-19: STUDI KASUS UNIVERSITAS GADJAH MADA - Kadek Aryana Dwi Putra; Fauzan Hidayatullah (BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, 2022)
Following a rigorous, carefully concerns and considered review of the article published in BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi to article entitled "LAYANAN PERPUSTKAAN PERGURUAN TINGGI DI MASA AWAL PANDEMI COVID-19: STUDI KASUS UNIVERSITAS GADJAH MADA" Vol 6, No 1 (2022).This paper has been found to be in violation of the BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi Vol. 14 No. 1 2022. Title: LAYANAN PERPUSTAKAAN PERGURUAN TINGGI DI MASA AWAL PANDEMI COVID-19: STUDI KASUS UNIVERSITAS GADJAH MADA. Authors: Kadek Aryana Dwi Putra, Fauzan Hidayatullah. DOI: https://doi.org/10.37108/shaut.v14i1.652.The document and its content has been removed from BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, and reasonable effort should be made to remove all references to this article.